2022
DOI: 10.1002/jhm.12805
|View full text |Cite
|
Sign up to set email alerts
|

Death among patients hospitalized with symptomatic COVID‐19: Implications for high‐risk patients

Abstract: Background: We aimed to examine the role played by the COVID-19 infection in patients' death and to determine the proportion of patients for whom it was a major contributor to death. Methods:We included patients ≥50 years old who were hospitalized with COVID-19 infection and died between March 1, 2020 and September 30, 2020 in a tertiary medical center. We considered COVID-19 infection to be a major cause for death if the patient had well-controlled medical conditions and death was improbable without coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast, the increase in deaths during the pandemic was re ected in the intermediate estimates, with these estimates showing more people in need of palliative care during the pandemic years than prepandemic. Even though COVID-19 was not included as a cause of death requiring palliative care in these estimates, the increase in need was due to a high proportion of the people who died with COVID-19 also having chronic health conditions that would bene t from palliative care (25,26,35). The intermediate estimates' exibility to account for underlying or contributory causes of death makes them more robust estimates of need than the minimal estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the increase in deaths during the pandemic was re ected in the intermediate estimates, with these estimates showing more people in need of palliative care during the pandemic years than prepandemic. Even though COVID-19 was not included as a cause of death requiring palliative care in these estimates, the increase in need was due to a high proportion of the people who died with COVID-19 also having chronic health conditions that would bene t from palliative care (25,26,35). The intermediate estimates' exibility to account for underlying or contributory causes of death makes them more robust estimates of need than the minimal estimates.…”
Section: Discussionmentioning
confidence: 99%
“…In these, the minimal estimates increased substantially (~ 10%), and the intermediate estimates increased slightly (~ 2%). The differing impacts on the minimal and intermediate estimates are because the conventional intermediate estimates, which account for contributory causes of death, already capture many COVID-19 deaths due to the high rates of comorbidities in people who die with COVID-19 (35).…”
Section: The Of Covid-19 Icd-10 Codes In the Methodologymentioning
confidence: 99%
“… 17 Although social and public interventions in countries reduce the adverse effects of COVID-19, recognizing the risk factors associated with COVID-19 severity and death in communities can help the health system identify high-risk groups and implement appropriate risk-reduction interventions. 18 , 19 In Iran, several social and non-pharmacological interventions have been performed to reduce the COVID-19 adverse effects, but recognizing the factors associated with the incidence of death and severity can provide comprehensive information on high-risk and low-risk groups. To our knowledge, separate studies have shown the relationship between some factors, but systematically, related risk factors have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In April 2022 issue, Stefan et al present findings from a retrospective cohort study examining patient characteristics of adults over age 50 with COVID-19 infection who died while hospitalized. 2 While some patients died unexpectedly due to COVID-19, approximately 60% had a serious or advanced illness with a potential prognosis of less than 12 months in the absence of COVID-19 infection. Among the patients in this study, over 40% had a diagnosis of dementia, and almost half (47%) were admitted from skilled nursing or long-term care facility.…”
mentioning
confidence: 99%